2021
DOI: 10.1126/sciimmunol.abe0896
|View full text |Cite
|
Sign up to set email alerts
|

The shared susceptibility epitope of HLA-DR4 binds citrullinated self-antigens and the TCR

Abstract: Individuals expressing HLA-DR4 bearing the shared susceptibility epitope (SE) have an increased risk of developing rheumatoid arthritis (RA). Posttranslational modification of self-proteins via citrullination leads to the formation of neoantigens that can be presented by HLA-DR4 SE allomorphs. However, in T cell–mediated autoimmunity, the interplay between the HLA molecule, posttranslationally modified epitope(s), and the responding T cell repertoire remains unclear. In HLA-DR4 transgenic mice, we show that im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
(74 reference statements)
0
20
0
Order By: Relevance
“…Moreover, the same TCR upon permanent re-expression into a stable T-cell line, generated a cit-TNC22-specific immune response with increased NFAT-GFP expression after cognate stimulation with cit-TNC22 HLA-monomeric complexes, again without any response towards another cit-TNC derived (cit-TNC17 HLA-monomers) (Fig. 2 c) or unrelated citrullinated fibrinogen derived peptide 11 (Fibβ-74cit 69-81 ) (Supp.Fig. 2) ligands.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the same TCR upon permanent re-expression into a stable T-cell line, generated a cit-TNC22-specific immune response with increased NFAT-GFP expression after cognate stimulation with cit-TNC22 HLA-monomeric complexes, again without any response towards another cit-TNC derived (cit-TNC17 HLA-monomers) (Fig. 2 c) or unrelated citrullinated fibrinogen derived peptide 11 (Fibβ-74cit 69-81 ) (Supp.Fig. 2) ligands.…”
Section: Resultsmentioning
confidence: 96%
“…Hence, it was important to validate the peptide-HLA tetramer results. Here, artificial re-expression of TCRs allows confirmation of antigen-specificity as well as further studies of structural and functional characteristics 10 , 11 . Thus, we single-cell sorted HLA tetramer-positive T cells for TCR sequencing from our short-term T cell lines (approximately at day 14).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on rheumatoid arthritis (RA) demonstrated that an ensemble of PTM in self-proteins could be involved in its pathogenesis, exemplified by the key role played by a protruding glycosylation in the immunodominant epitope CII 256-270 derived from the type II collagen CII protein in the elicitation of autoreactive T cells ( Michaëlsson et al, 1994 ). Studies of self-peptides associated with RA revealed a strong correlation between citrullination of arginine at peptide position p4 and epitope binding affinities to HLA-DRB1 ( Scally et al, 2013 ; Ting et al, 2018 ; Lim et al, 2021 ). Others demonstrated that citrullination of several arginine residues in α-enolase-derived peptides elicited significant functional CD4 + T cell responses in primary cells from RA patients ( Gerstner et al, 2016 ; Pieper et al, 2018 ).…”
Section: Major Histocompatibility Complexes-bound Chemically Modified...mentioning
confidence: 99%
“…In another recent study [12], we examined the αβTCR repertoire in a mouse model of Rheumatoid Arthritis that expresses the human susceptibility allele HLA-DRB1*04:01.…”
Section: Extended Analysis Of Drug-induced Human αβTcrs Reveals a Cen...mentioning
confidence: 99%
“…The demonstration data is from Mifsud et al (2021) [14] and Lim et al (2021) [12]. The local version of 'TCR_Explore' and all the raw data files and processed datasheets are located on GitHub https://github.com/KerryAM-R/TCR_Explore in the test-data section.…”
Section: Data and Code Availabilitymentioning
confidence: 99%